Effectiveness of Localized Injection of Botulinum Toxin versus Localized Injection of Steroids (Triamcinolone) in the Treatment of Keloids - رومية عبد الحليم; ميهوب أماني (Latakia University Journal -Medical Sciences Series, 2020)
Objective: Keloid pose aesthetic and functional problems, in addition to being associated with disturbing clinical symptoms such as itching and pain, and current methods of treatment are limited in effectiveness. Clinical studies indicate that botulinum toxin (BTA) may prevent the formation of keloid and treat it, so the aim of this research was to compare the effectiveness of topical injection of botulinum toxin versus topical steroid injection in the treatment of keloid. Methods: The research sample included 23 patients from the dermatology clinic at Tishreen University Hospital in Lattakia between 2019 and 2020, with keloids. The number of keloids registered with the studied sample was 30 distributed to two groups: Group A receiving IL steroid repeated every 4 weeks for six sessions, Group B IL BTA 5 IU /cm3 repeated every 8 weeks for three sessions. Objective parameters (hardness, elevation, pigmentation and vasscularity), subjective complaints (itching, pain, and tenderness), patient satisfaction, and side effects were evaluated. Results: There was a 58.4% decrease in the Vancouver scale for group A, and 65.8% for group B, without a statistical difference between the two groups (P <0.05). A noticeable decrease in tenderness 85.9% in treatment group A and 82.7% in treatment group B. A significant decrease in elevation in A 79.4% while B had a slight decrease of 27%. For vascularity we observed a slight decrease in treatment group A of 17.7% without statistical significance, whereas in treatment group B there was a decrease of 58%. The itching improvement in treatment group B was shown to be greater with statistically significant differences (P<0.05). Skin atrophy and telangiectasia were evident in 11 patients of group A. Conclusions: This study showed the efficacy and safety of topical toxin injection in treating keloid by improving objective and subjective criteria when compared to topical injection of corticosteroids. With fewer side effects reported for botulinum toxin.